C–H bond activations by the HO˙/(Salophent-Bu)Co(ii) radical pair generated via homolysis of a terminal Co(iii)–OH bond. Issue 22 (23rd February 2023) - Zhang, Jia; Li, Songyi; Fang, Huayi
Abstract : The reactive HO˙/(Salophen t -Bu )Co(ii ) radical pair was generated via a terminal Co(iii )–OH bond homolysis in hydroxocobalt(iii ) complexes. Based on this process, C–H bond activations in different substrates were achieved under ambient conditions. Abstract : The reactive HO˙/(Salophen t -Bu )Co(ii ) radical pair was observed to be generated via homolysis of the terminal Co(iii )–OH bond in transient (Salophen t -Bu )(L)Co(iii )(OH) (L = Py, MeOH) complexes as indicated by UV-Vis and EPR measurements. Based on this elementary process, C–H bond activations in acetone, 2-butanone, acetonitrile and benzene were achieved under ambient conditions. For the reactions of the first three substrates, the alkylcobalt(iii ) complexes were formed as the products.